2015
DOI: 10.1007/s40948-015-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Coal permeability model on the effect of gas extraction within effective influence zone

Abstract: In situ gas extraction is the main measure adopted by mines to achieve mining safety standards. Coal permeability is significantly influenced by coal shrinkage during gas release. Based on effective stress and additional damage that resulted from gas extraction, a unique model was proposed to describe the spatial and temporal distribution of coal permeability within the effective influence zone. Calculation models for the conditions of one and two extracting boreholes were developed. A parametric study on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Coal generally has a mixture of pore fluid, composed of water, N 2 , CO 2 and CH 4 and their composition can be changed with various applications such as CO 2 sequestration and N 2 injection for ECBM recovery. It is therefore necessary to have comprehensive knowledge of the relative effect created by each component.…”
Section: How Significant Is Water and N 2 Saturation On Coal Strengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Coal generally has a mixture of pore fluid, composed of water, N 2 , CO 2 and CH 4 and their composition can be changed with various applications such as CO 2 sequestration and N 2 injection for ECBM recovery. It is therefore necessary to have comprehensive knowledge of the relative effect created by each component.…”
Section: How Significant Is Water and N 2 Saturation On Coal Strengthmentioning
confidence: 99%
“…The process of enhanced coal bed methane (ECBM) recovery is being implemented and tested as a viable option to store and reduce the amount of anthropogenic carbon dioxide (CO 2 ) in the Earth's atmosphere, as well as for the recovery of useful coal bed methane (CH 4 ) gas [1][2][3][4][5][6][7]. Overall, the ECBM process involves introducing CO 2 through injecting wells into deep coal seams and this CO 2 then acts as a displacing gas, which allows the already adsorbed CH 4 to be desorbed from the coal matrix.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor knowledge of the characteristics of strata movement due to longwall mining can create very serious ground hazards, potentially jeopardizing the safety and lives of mine personnel, as well as affecting the productivity and efficiency of a mining operation. For decades, extensive effort has been paid to study the strata movement and stress distribution law induced by mining excavation and obtain comprehensive understanding of the permeability evolution of coal seam (Chen et al 2014;Xie et al 2015;Yang et al 2011a, b) and a proper design of a coal pillar (Chugh et al 1990;Hammy and Fejes 1992;Holla 1997;Holla and Buizen 1991a;Islam et al 2009). Holla and Buizen (1991b) performed an empirical study of the sub-surface deformation caused by retreating longwall mining and monitored the strata movement over a longwall panel and indicated that the three-joint-arch structure formed by the broken key roof stratum is monotonically unstable structure and its limit value is determined by the breaking convergence value.…”
Section: Introductionmentioning
confidence: 99%